2021
DOI: 10.1111/jfpp.15414
|View full text |Cite
|
Sign up to set email alerts
|

Detection of fructophilic lactic acid bacteria (FLAB) in bee bread and bee pollen samples and determination of their functional roles

Abstract: In this study, bee bread and bee pollen samples were characterized in terms of presence of fructophilic lactic acid bacteria (FLAB). Following discrimination and identification of FLAB strains, their functional roles were determined. Genotypic characterization of FLAB strains revealed the presence of 27 distinct strains belonging to Lactobacillus kunkeei (21), Fructobacillus fructosus (3), Lactobacillus plantarum (2), and Leuconostoc mesenteroides (1) strains. In terms of functional roles, all FLAB strains dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
(97 reference statements)
1
9
1
Order By: Relevance
“… [ 21 ] Fructose, Glucose, Turanose, and Maltose HPLC-DAD Romania and India Five samples (Brassicaceae, Poaceae, Myrtaceae, Rutaceae, Asteraceae, Fabaceae, Tiliaceae, Fabaceae, Rosaceae, Plantaginaceae, Fabaceae, Asteraceae, Lamiaceae, Salicaceae, Rosaceae, and Fagaceae) [ 22 ] Fructose, Glucose, Sucrose, and Maltose HPLC coupled with an ELSD Malaysia Four multifloral samples ( Mimosa pudica, Sphagneticolatrilobata, Bidens ilosa, Cassia sp, Areca catechu, Peltophorumpterocarpum, Phaleria capitata, Cassia siamea, Citrus aurantifolia, and Ageratum conyzoides ) [ 11 ] Microorganisms Lactobacillus kunkeei RAPD-PCR Turkey Four samples (not identified). [ 60 ] Cladosporium, Penicillium, Alternaria, Monilinia, Sclerotina, Ascosphaera, Toxicocladosporium, Botrytis, Pseudopithomyces, Camerosporium, Paraconiothyrium, Podosphaera, Golovinomyces, Paraphaeosphaeria, Periconia, and Septoriella NGS-sequencing Bulgaria Four samples (not identified). [ 54 ] Apilactobacilluskunkeei, Lactiplantibacillus plantarum, Fructobacillusfructosus, Levilactobacillus brevis, and Lactobacillus delbrueckii PCR-DGGE analysis RAPD-PCR analysis Italy Twelve samples (not identified) [ 55 ] Organic acids Oxalic acid …”
Section: Bee Bread Compositionmentioning
confidence: 99%
“… [ 21 ] Fructose, Glucose, Turanose, and Maltose HPLC-DAD Romania and India Five samples (Brassicaceae, Poaceae, Myrtaceae, Rutaceae, Asteraceae, Fabaceae, Tiliaceae, Fabaceae, Rosaceae, Plantaginaceae, Fabaceae, Asteraceae, Lamiaceae, Salicaceae, Rosaceae, and Fagaceae) [ 22 ] Fructose, Glucose, Sucrose, and Maltose HPLC coupled with an ELSD Malaysia Four multifloral samples ( Mimosa pudica, Sphagneticolatrilobata, Bidens ilosa, Cassia sp, Areca catechu, Peltophorumpterocarpum, Phaleria capitata, Cassia siamea, Citrus aurantifolia, and Ageratum conyzoides ) [ 11 ] Microorganisms Lactobacillus kunkeei RAPD-PCR Turkey Four samples (not identified). [ 60 ] Cladosporium, Penicillium, Alternaria, Monilinia, Sclerotina, Ascosphaera, Toxicocladosporium, Botrytis, Pseudopithomyces, Camerosporium, Paraconiothyrium, Podosphaera, Golovinomyces, Paraphaeosphaeria, Periconia, and Septoriella NGS-sequencing Bulgaria Four samples (not identified). [ 54 ] Apilactobacilluskunkeei, Lactiplantibacillus plantarum, Fructobacillusfructosus, Levilactobacillus brevis, and Lactobacillus delbrueckii PCR-DGGE analysis RAPD-PCR analysis Italy Twelve samples (not identified) [ 55 ] Organic acids Oxalic acid …”
Section: Bee Bread Compositionmentioning
confidence: 99%
“…It provides easily digestible carbohydrates, proteins, fats, minerals, and vitamins for the bee larvae and the adult bees, but also acts as a functional food (feed), possessing antioxidant and anti-inflammatory properties [1][2][3]. Even though many studies in the last years have been focused on the bacterial composition of bee bread [4][5][6], those on fungal composition are rather scarce despite the publication of some of them dating from the '80s [7]. An exception is the study of Tauber et al [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that mice treated with LGG had lower symptoms frequency and higher survival rates than control. Also, increased mRNA expression of IL-8, TNF, and MCP-1 (monocyte chemotactic protein) were noticed in Ispirli and Dertli ( 183 ).…”
Section: Potential Therapeutic Properties Of Labs Found In Bb And/or ...mentioning
confidence: 96%